2018
DOI: 10.3390/ijms19092689
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Comparison between Brassica napus Genic Male Sterile Line and Restorer Line

Abstract: DNA methylation is an essential epigenetic modification that dynamically regulates gene expression during plant development. However, few studies have determined the DNA methylation profiles of male-sterile rapeseed. Here, we conducted a global comparison of DNA methylation patterns between the rapeseed genic male sterile line 7365A and its near-isogenic fertile line 7365B by whole-genome bisulfite sequencing (WGBS). Profiling of the genome-wide DNA methylation showed that the methylation level in floral buds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 47 publications
8
16
0
Order By: Relevance
“…However, studies have also shown that DNA methylation is not necessarily associated with the repression of gene expression, but exhibits the positive correlations with transcription activation instead [52]. In the study of Brassica napus, the gene expression of BnaA0724700D and BnaA08g08410D are up-regulated, although they exhibit opposite methylation patterns in their promoters [53]. In the present study, the increased methylation in CHH type were at the gene body region of Grb10, eIF4E and mTOR genes.…”
Section: Discussionsupporting
confidence: 38%
“…However, studies have also shown that DNA methylation is not necessarily associated with the repression of gene expression, but exhibits the positive correlations with transcription activation instead [52]. In the study of Brassica napus, the gene expression of BnaA0724700D and BnaA08g08410D are up-regulated, although they exhibit opposite methylation patterns in their promoters [53]. In the present study, the increased methylation in CHH type were at the gene body region of Grb10, eIF4E and mTOR genes.…”
Section: Discussionsupporting
confidence: 38%
“…It encodes a deleterious chimeric protein that localises to the chloroplast, affects normal function of the chloroplast to cause aborted anthers and albinotic seedlings, and high temperature treatment can partially restore male fertility caused by Bnams4 b Xia et al, 2016). Bnams4 a is a suppressor gene and may reduce the transcription level of Bnams4 b through DNA methylation Wang et al, 2018). Bnams4 c is a null allele .…”
Section: Introductionmentioning
confidence: 99%
“…The consistent demethylation of the cytosines in the promoter region of PPR, the consistent methylation of the cytosines in the downstream region of bZIP, as well as the stable methylation state in the downstream regions of MYB and C2H2 contribute to rice heat tolerance [46]. Several additional TFs, including flowering control locus A (FCA), bZIP, tryptophan-arginine-lysinetyrosine (WRKY), APETALA2 (AP2), cysteine 8-cysteine 5 or cysteine 3-histidine-type zinc finger protein (C8C5C3H), and DNA binding with one finger protein (Dof), were also reported to be regulated by DNA methylation in plants [49][50][51]. The post-transcriptional regulator FCA, which has two RNAbinding motifs (RRMs), upregulates the gene mitogen-activated protein kinase 5 lacking an intact kinase domain (OstMAPKKK5).…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytosines in the promoter or downstream region of the TFs MYB and C2H2 could be HNT-induced demethylated in the heat-sensitive rice strain but were unchanged in the heat-sensitive strain, which might allow for the removal of excessive ROS and reduction of cellular damage in the heat-tolerant strain. SnRK2 also plays important roles in sugar transport and starch synthesis by regulating bZIP, WRKY80, AP2, and C8C5C3H [48][49][50]58]. The cytosines in the promoter or downstream regions of bZIP and WRKY80 were HNT-induced methylated, while the cytosines in the promoter or downstream regions of AP2 and C8C5C3H were unchanged in the heat-tolerant rice strain.…”
Section: Discussionmentioning
confidence: 99%